مكافحة الفساد الإداري دراسة مقارنة بين الشريعة والقانون - أميرة قرايرية; إلهام قمادنية (My University, 2018)
Summary: Administrative corruption is an organ that undermines the credibility of the state. It is an epidemic that grunts the entity of society in general and the entity of the administration with a special deal. Because the diagnosis of the problem is the first stage of the fight, we have identified the phenomenon of corruption by identifying the various definitions of it in terms of both sharia and law, while showing its multiple images. In order to limit this situation, we have addressed mechanisms for preventing and combating administrative corruption that have dealt with crimes of administrative corruption in the public sector. For example, we took the crime of bribery, the crime of embezzlement, and adjudicated each crime with the prescribed penalties set for it both by Islamic law and by law. .................... ملخص : الفساد الإداري جهاز يضرب مصداقية الدولة، فهو وباء ينخر كيان المجتمع بصفة عامة و كيان الإدارة بصفقة خاصة، و لأن تشخيص المشكلة هو أول مراحل المكافحة فقد قمنا بتحديد ظاهرة الفساد و ذلك بالتعرف على مختلف تعاريفه سواء من حيث الشريعة أو القانون، مع بيان صوره المتعددة. وسعيا لمحد من هذه الظاىرة فقد تناولنا آليات الوقاية من الفساد الإداري و مكافحته التي عالجت جرائم الفساد الإداري في القطاع العام. و أخدنا على سبيل المثال جريمة الرشوة، جريمة الاختلاس، وفصلنا في كل جريمة مع تحديد العقوبات المقررة لها سواء من جانب الشريعة الإسلامية أو القانون. ........................ Résumé : La corruption administrative est un dispositif qui frappe la crédibilité de l'Etat, une pandémie qui détruit la société en général et l'entité de gestion dans un accord spécial، le diagnostic du problème étant les premières étapes du contrôle, nous identifions le phénomène de la corruption. Afin de réduire ce phénomène, nous avons abordé les mécanismes de prévention et de contrôle de la corruption administrative, qui traitent des crimes de corruption administrative dans le secteur public. Par exemple, nous avons trouvé le crime de corruption, le crime de détournement de fonds, et la séparation de chaque crime avec la détermination des peines qui leur sont prescrites, que ce soit par la loi ou la loi islamique.